Respostas
respondido por:
1
x3 + x2 = 2x
x3 + x2 -2x = 0
x(x2 +x 2) = 0
x'= 0 (uma das raízes)
temos x2 + x -2= 0
delta = b2 -4ac
delta = 1 -4(1)(-2) = 1 + 8 = 9
x'' = -b + raiz quad delta/2a
x'' = -1 + 3/2, ou
x'' = 2/2 = 1
x''' = -b - raiz quad delta/2a
x''' = -1 -3/2 = 4/2 =- 2
S ={0, 1, -2}
x3 + x2 -2x = 0
x(x2 +x 2) = 0
x'= 0 (uma das raízes)
temos x2 + x -2= 0
delta = b2 -4ac
delta = 1 -4(1)(-2) = 1 + 8 = 9
x'' = -b + raiz quad delta/2a
x'' = -1 + 3/2, ou
x'' = 2/2 = 1
x''' = -b - raiz quad delta/2a
x''' = -1 -3/2 = 4/2 =- 2
S ={0, 1, -2}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás